Media audiences : television, meaning and emotion - Gorton, Kristyn, 1972- (Media topics., 2009)
An engaging and original study of current research on television audiences and the concept of emotion, this book offers a unique approach to key issues within television studies. Topics discussed include: television branding; emotional qualities in television texts; audience reception models; fan cultures; 'quality' television; television aesthetics; reality television; individualism and its links to television consumption. The book is divided into two sections: the first covers theoretical work on the audience, fan cultures, global television, theorising emotion and affect in feminist theory and film and television studies. The second half offers a series of case studies on television programmes such as Wife Swap, The Sopranos and Six Feet Under in order to explore how emotion is fashioned, constructed and valued in televisual texts. The final chapter features original material from interviews with industry professionals in the UK and Irish soap industries along with advice for students on how to conduct their own small-scale ethnographic projects. Key Features: An accessible guide to theoretical work on emotion and affect, this book is key reading for advanced undergraduates and postgraduates doing media studies, communication and cultural studies and television studies. Case studies on emotion and television in British and US media contexts demonstrate new research and provide a starting point for readers undertaking their own research. Each chapter includes exercises, points for discussion and lists for further reading